2021
DOI: 10.1177/2192568220985470
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Fusion Surgery for Patients With Back Pain and Degenerative Disc Disease: An Observational Study From the Canadian Spine Outcomes and Research Network

Abstract: Study Design: Uncontrolled retrospective observational study. Objectives: Surgery for patients with back pain and degenerative disc disease is controversial, and studies to date have yielded conflicting results. We evaluated the effects of lumbar fusion surgery for patients with this indication in the Canadian Spine Outcomes and Research Network (CSORN). Methods: We analyzed data that were prospectively collected from consecutive patients at 11 centers between 2015 and 2019. Our primary outcome was change in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 63 publications
0
12
1
Order By: Relevance
“…We tested for changes in mean patient-reported leg pain, back pain, disability, and function, and we interpreted these changes using Minimal Clinically Important Differences (MCIDs), which are the smallest magnitude treatment effects that informed patients are likely to perceive as beneficial enough to justify changes in their management. 25,26 We implemented the following MCIDs, which have been established elsewhere: 21,27,28 NPRS leg pain – 1.6 points, NPRS back pain – 1.2 points, ODI – 12.8 points, SF12 PCS – 3.3 points, SF12 MCS – 3.8 points.…”
Section: Methodsmentioning
confidence: 99%
“…We tested for changes in mean patient-reported leg pain, back pain, disability, and function, and we interpreted these changes using Minimal Clinically Important Differences (MCIDs), which are the smallest magnitude treatment effects that informed patients are likely to perceive as beneficial enough to justify changes in their management. 25,26 We implemented the following MCIDs, which have been established elsewhere: 21,27,28 NPRS leg pain – 1.6 points, NPRS back pain – 1.2 points, ODI – 12.8 points, SF12 PCS – 3.3 points, SF12 MCS – 3.8 points.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously noted similar attrition in Canadian Spine Outcomes and Research Network among patients with DCM and patients with other pathologies, which is suboptimal. 4,10,[23][24][25] However, these losses still left us with 70% of eligible participants and a relatively large sample size of 330. Interestingly, our finding of 98% or greater completion of PROMs vs 73% completion of clinician-reported mJOA scores at 2 years suggests that getting surgeons to complete follow-up outcome measures may in fact be more challenging than getting patients to complete them.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Many limitations and strengths of the CSORN research platform and observational analyses of this dataset have been described previously. 12,13,18,19 One of the main limitations of this study is that our radiographic data were limited to the cervical spine alone, which means that we were not able to consider global sagittal and spinopelvic parameters. Some studies have demonstrated associations between global alignment and outcomes in the setting of cervical deformity, but there is uncertainty about whether global alignment parameters should be routinely evaluated in all patients with CSM when the effects of local morphology have not been established.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Missing data raise the possibility of spurious or misleading results, but we showed that these patients did not have different baseline characteristics in comparison to those included, and we have previously shown similar interim outcomes among CSORN participants when long-term data are unavailable. 13,18,20,21 Our sample size despite these exclusions is the largest published with radiographic measurements to date, and this study is one of only few with prospective data collection and PROMs. 9,22,23 Our study is also limited in that we did not perform an a priori sample size calculation.…”
Section: Limitations and Strengthsmentioning
confidence: 99%